PVDF/Clay Spheres Obtained through Phase Inversion for Cu Ion Removal - Dias, Gabriel C. [UNESP]; Cardoso, Mayk F. [UNESP]; Sanches, Alex O. [UNESP]; Santos, Mirian C. [UNESP]; Malmonge, Luiz F. [UNESP] (MDPI, 2023)
In this study, spheres of poly (vinylidene fluoride)/clay were synthesized using an easy dripping method (also known as phase inversion). The spheres were characterized by scanning electron microscopy, X-ray diffraction, and thermal analysis. Finally, application tests were carried out using commercial cachaça, a popular alcoholic beverage in Brazil. The SEM images revealed that during the solvent exchange process for sphere formation, PVDF tends to form a three-layered structure with a low-porosity intermediate layer. However, the inclusion of clay was observed to reduce this layer and also widen the pores in the surface layer. The results of the batch adsorption tests showed that the composite with 30% clay content in relation to the mass of PVDF was the most effective among those tested, with the removal of 32.4% and 46.8% of the total copper present in the aqueous and ethanolic media, respectively. The adsorption of copper from cachaça in columns containing cut spheres resulted in adsorption indexes above 50% for samples with different copper concentrations. Such removal indices fit the samples within the current Brazilian legislation. Adsorption isotherm tests indicate that the data fit better to the BET model.
Keywords: adsorptive copper; clay spheres; drip method; polymer composite; PVDF